The movement from monoliths to component-based network elements. - Bjorkman, N. (IEEE Communications magazine)
To be competitive in a rapidly growing market requires rapid upgrades to the performance and functionality of the network. One way to manage rapid upgrades of the network with minimum risk is to deploy equipment using a modular system architecture. Modularity allows a network operator to mix and match best of breed components to achieve the desired system rather than rely on vendors to implement specific technology before making crucial business decisions. This article begins with an overview of the current global movement toward standards that support network elements with modular system architecture. The story begins with university initiatives and the forming of OpenSig and IEEE P1520 more than five years ago, continuing with related and complementary initiatives by the Parlay Group, Softswitch Consortium, Multiservice Switching Forum, and several IETF working groups. Next, special attention is given to the component-based architecture of the Multiservice Switching Forum released in summer 2000. The trend of building network equipment from components with distinctly different functional specialties is described in three examples: media gateways, IP routers, and virtual IP routers. It is envisioned that component-based network infrastructure will spawn new markets for entrepreneurial developers, spurring competition and accelerating the creation of innovative solutions for all facets of global communications. The article concludes with a smorgasbord of new market opportunities